1999
DOI: 10.1046/j.1464-410x.1999.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

The tolerability of urodynamic studies and flexible cysto‐urethroscopy used in the assessment of men with lower urinary tract symptoms

Abstract: In contrast with earlier results, this clinic-based urodynamic investigation was associated with a low proportion of urinary tract infection, and low objective and subjective morbidity. The combination of a urodynamic study with a flexible cysto-urethroscopy does not cause significant additional voiding complaints. Most patients find urodynamic studies tolerable and not very bothersome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
5
19
0
Order By: Relevance
“…Also other symptoms in our study are comparable or less as reported in literature. The frequency of urinary tract infections in our study is comparable to that after cystoscopy only [16][17][18][19]. Our overall frequency of hematuria after cystoscopy and TURB was 13.7%, compared to reported gross hematuria after flexible cystoscopy in 19% [17].…”
Section: Commentsupporting
confidence: 71%
See 1 more Smart Citation
“…Also other symptoms in our study are comparable or less as reported in literature. The frequency of urinary tract infections in our study is comparable to that after cystoscopy only [16][17][18][19]. Our overall frequency of hematuria after cystoscopy and TURB was 13.7%, compared to reported gross hematuria after flexible cystoscopy in 19% [17].…”
Section: Commentsupporting
confidence: 71%
“…Although this is daily practice for any urologist, literature on quantitative analysis of typical complications occurring after cystoscopy with rigid scopes and biopsies or TURB are very sparse. The complications after flexible cystoscopy are better reported, and even flexible cystoscopy is reported to cause urgency and increased voiding frequency in 35% to 40% of patients, and complaints of pain are reported in 20% to 50% of patients [16,17]. Compared to our study, where rigid cystoscopy and TUR are applied, procedural pain and other urinary disorders and are found in approximately 5% and 25% after HAL-BLC and WL (table 4), and in 11.9% and 33.6% in those patients were HAL-BLC and WL were combined (table 5).…”
Section: Commentmentioning
confidence: 99%
“…Our study identified an incidence of postflexible-cystoscopy dysuria of 28%, which is at the lower end of the range when compared with reports in the literature (30-54% [1,2,11]). As the incidence found was lower than expected, the sample size of the study was adequate to detect a 50% reduction in dysuria, rather than the 33% reduction specified in the study design.…”
Section: Discussionsupporting
confidence: 52%
“…Cystoscopy is a common urological procedure, and painful voiding (dysuria) is frequently reported afterwards with an incidence of 30-54% [1,2]. Relief is often attempted through the use of alkalinizing agents such as Ural® (sodium bicarbonate 1.76 g, sodium citrate (anhyd) 0.63 g, citric acid (anhyd) 0.72 g, tartaric acid 0.89 g, saccharin sodium 1.4 mg per 4 g, $1.27 AUD (70p) for 2 days, Sigma Pharmaceuticals, Australia Pty Ltd).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the cost-effectiveness of MA in the surveillance of patients with NMI bladder cancer we initiated a large multicentre study, including a quality-of-life component. Few studies have systematically evaluated the impact of CUS as perceived by patients [12][13][14][15][16]. The present study aimed to evaluate the burden of CUS as perceived by patients in a randomized comparison with patients monitored by MA of urinary samples.…”
Section: Introductionmentioning
confidence: 99%